Optimization of synergistic energy storage density and efficiency for eco-friendly (Na0.5Bi0.5)0.6Sr0.4TiO3-based relaxor ferroelectric ceramics - Hu Di; Pan Zhongbin; Wu Lukang; Yang Fan; Tang Luomeng; Zhao Jinghao; Shen Yihao; Chen Yuyun; Li Peng; Zhai Jiwei; Liu Jinjun (Journal of Materiomics, 2021)
Inspired by increasing demand of advanced pulsed power capacitors, the development of lead-free dielectric ceramic capacitors with high energy storage density and temperature-insensitive performance are extremely crucial. Herein, the lead-free relaxor ferroelectric ceramics based on (1-x) (Na0.5Bi0.5)0.6Sr0.4TiO3- xSr0.7La0.2ZrO3 [abbreviated as (1-x)NBST-xSLZ] are prepared by the solid-state reaction route. The large recoverable energy density (Wrec) of 3.45 J/cm3 and efficiency (η) of 90.1% are simultaneously realized in 0.86NBST-0.14SLZ ceramic due to increased breakdown strength. Furthermore, both the Wrec and η of 0.86NBST-0.14SLZ ceramic display superior of thermal stability (20–180 °C), frequency stability (1–1000 Hz), and cycle stability (104) within a satisfactory range of variation. In addition, the 0.86NBST-0.14SLZ ceramic can also achieve a large current density (CD) of 625 A/cm2, an ultrahigh power density (PD) of 50 MW/cm3 and a fast discharge rate (τ0.90) of 160.8 ns at 160 kV/cm. These results demonstrate that the 0.86NBST-0.14SLZ ceramic could be a highly competitive and eco-friendly relaxor ferroelectric material for next-generation pulsed power capacitors.